The Effect Of Work Discipline And Work Motivation On Employee Performance Dinas Pemadam Kebakaran Dan Penyelamatan Kota Bengkulu - Jepita Sari; Islamuddin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to find out whether work discipline, work motivation affect the performance of employees at the Bengkulu City Fire and Rescue Service. This research is a type of quantitative research. Data collection techniques are observation, interviews and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Work discipline (X1) influences employee performance (Y) at the Bengkulu City Fire Department. Work motivation (X2) has a positive and significant effect on employee performance (Y) at the Bengkulu City Fire Department. Work discipline (X1) and work motivation (X2) affect employee performance (Y) at the Bengkulu City Fire Department.